2021
DOI: 10.1007/s11302-020-09760-9
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the purinergic pathway in breast cancer and its therapeutic applications

Abstract: Breast cancer (BC) is the most frequent cause of death among women, representing a global public health problem. Here, we aimed to discuss the correlation between the purinergic system and BC, recognizing therapeutic targets. For this, we analyzed the interaction of extracellular nucleotides and nucleosides with the purinergic receptors P1 and P2, as well as the influence of ectonucleotidase enzymes (CD39 and CD73) on tumor progression. A comprehensive bibliographic search was carried out. The relevant article… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 220 publications
(353 reference statements)
1
10
0
Order By: Relevance
“…The CD39 /CD73/A2AR signaling pathway has been shown to be associated with poor cancer prognosis. In addition, CD39 and CD73 are also involved in the formation of new lymphatic vessels around tumors and progression of malignant tumors such as breast carcinoma, multiforme glioblastoma and chronic lymphocytic leukemia [ 78 80 ]. Importantly, the blockade of adenosine/A2AR pathway resulted in the enhancement of cancer chemotherapy and immunotherapy in numerous cancer types including lung adenocarcinoma, renal clear cell carcinoma, pheochromocytoma and paraganglioma [ 43 , 81 83 ].…”
Section: The Expression and Function Of Cd39/cd73/a2ar In Various Can...mentioning
confidence: 99%
“…The CD39 /CD73/A2AR signaling pathway has been shown to be associated with poor cancer prognosis. In addition, CD39 and CD73 are also involved in the formation of new lymphatic vessels around tumors and progression of malignant tumors such as breast carcinoma, multiforme glioblastoma and chronic lymphocytic leukemia [ 78 80 ]. Importantly, the blockade of adenosine/A2AR pathway resulted in the enhancement of cancer chemotherapy and immunotherapy in numerous cancer types including lung adenocarcinoma, renal clear cell carcinoma, pheochromocytoma and paraganglioma [ 43 , 81 83 ].…”
Section: The Expression and Function Of Cd39/cd73/a2ar In Various Can...mentioning
confidence: 99%
“…As one of the P1 receptors, ADORA2A is involved in the proliferation and invasion of breast cancer [15]. Adenosine Interaction with ADORA2A Promotes Gastric Cancer Metastasis [16].…”
Section: Discussionmentioning
confidence: 99%
“…It still needs to be further explored. In breast cancer, it was reported that P2X7 has a dual function in some cancer, for example, when activated for a short time, P2X7 promotes metastasis, but when activated for long periods, it is related to breast cancer cell death [ 40 ]. The dual function of P2X7 in different stages of tumor is led by fine-tuning regulation of multiple miRNAs.…”
Section: Purinergic Signalling Modulated By Mirnas In Cancersmentioning
confidence: 99%